Mechanisms of Action of Ig Preparations: Immunomodulatory and Anti-Inflammatory Effects - Matucci, Andrea; Maggi, Enrico; Vultaggio, Alessandra (Frontiers in Immunology, 2015)
Primary immunodeficiency (PID) disorders that predispose patients to recurrent infections require immunoglobulin (Ig) replacement therapy. Ig replacement therapy has been stated as beneficial, although the optimal IgG trough level to be maintained over time in order to minimize infectious risk has not been established. The most common route of administration of Ig has been intravenously, although there are different options, one of them being the subcutaneous route. Ig replacement therapy has been a life-saving treatment for patients suffering from primary and secondary antibody immunodeficiency. The key role of regular Ig replacement in patients with antibody deficiencies is related to the ability to provide specific antibodies that could not be produced by these patients as demonstrated by the reduction of severe infections such as meningitis and pneumonia. The therapeutic benefits of Ig may also be due to an active role in various anti-inflammatory and immunomodulatory activities, which may complicate the clinical picture of PID. Anti-inflammatory activities are seen more generally when intravenous Ig is administered at high dose. The immunomodulatory and anti-inflammatory activities are important not only in the treatment of autoimmune diseases but also in patients suffering from immunodeficiency.